Knowledge level of health workers on hand hygiene, aseptic techniques, isolation and quarantine services in selected health facilities in Kiambu County, Kenya - Njuguna, Judy Wanjiku; Kimani, Harun; King’ori, Isabell (International Journal Of Community Medicine And Public Health, 2022)
Background: The objective of this article was to ascertain the knowledge level of health workers on hand hygiene, aseptic techniques, isolation and quarantine services in selected health facilities in Kiambu County. Methods: A descriptive cross-sectional research design was adopted in Kiambu County and Thika Sub-County was purposively selected. Stratified random sampling was used to draw a sample size of 261 study respondents. Both descriptive and inferential statistics were used to analyze the data. Results: Out of the 261 questionnaires administered, only 178 were accurately, appropriately filled and returned. Chi square was used to test the association between independent and dependent variables at 95% confidence interval. A p value of less than 0.05 (p<0.05) was considered statistically significant. The general knowledge of health workers on IPC was satisfactory with 135 (75.8%) having good knowledge. Knowledge was established to have statistically significant association with nosocomial prevalence (χ2 =49.45, df =2, p<0.001). Conclusions: It was concluded that majority of health workers had good knowledge on hand hygiene and aseptic techniques but in the contrary this was not the case with isolation and quarantine services. This could have been attributed to the fact that there were almost no trainings carried out on isolation and quarantine services and furthermore not all health facilities had the infrastructure for isolation and quarantine required to enforce those services.